1989
DOI: 10.1136/bmj.298.6665.50-c
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the acute phase response.

Abstract: Breach of this standard is ipso facto malpractice. Furthermore, responsibility for professional acts rests with the actUal treatihg physician and may not be trahsferted to leiployers, government programnmes, hospital officials or commnittees, chiefs of service, comftiiWs §onets, atid the like. We have no professional dMty to any such party; our obligatlon is solely t6 out patienits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Dupont and Page have noted that flattened cysts are larger than apocrine cysts and suggested that flattened cysts represent a stage of development in which the active element is no longer present. 5 Our evidence was that the type of breast cyst was not constant in individual patients. Indeed, in the report of Bruzzi et al 60 of 120 patients with multiple cysts had a mixture of type I (high potassium concentrations) and type II (low potassium concentrations) cysts.…”
Section: Consistency Of Cyst Type Needs To Be Knownmentioning
confidence: 70%
See 2 more Smart Citations
“…Dupont and Page have noted that flattened cysts are larger than apocrine cysts and suggested that flattened cysts represent a stage of development in which the active element is no longer present. 5 Our evidence was that the type of breast cyst was not constant in individual patients. Indeed, in the report of Bruzzi et al 60 of 120 patients with multiple cysts had a mixture of type I (high potassium concentrations) and type II (low potassium concentrations) cysts.…”
Section: Consistency Of Cyst Type Needs To Be Knownmentioning
confidence: 70%
“…5 He hopes that, after the publication of the data from the DIGAMI study, clinicians will not be reluctant to introduce insulin treatment; on the basis of the results of this single study, however, this approach would be premature.…”
Section: Factors Other Than Continued Use Of Subcutaneous Insulin Maymentioning
confidence: 99%
See 1 more Smart Citation